Analysis of shrines properties using remote sensing approach: case study of Lembah Bujang - Hj. Mohd. Noor, Norzailawati; Roslan, Shairatul Akma; Md Ali, Zuraini (2015)
The heritage of Lembah Bujang is important as a starting point to understand the origins and history of civilization in Malaysia. This research is to analyze the spectral reflectance of shrines properties in an identified area by using remote sensing techniques in conserving heritage site of Lembah Bujang, Kedah, Malaysia. The remote sensing device (Spectroradiometer) was used to measure the spectral power distribution of source of shrines in the study area. This tool was applied for reflectance’s test over properties such as clays, granite, literates and iron in a different two study areas consist of Lembah Bujang and Sungai Batu. Remote sensing test properties demonstrate that discrimination of properties types of each civilization is possible through reflection measurement, but that discrimination is complicated by surface conditions, such as weathering and lichen growth. Comparison between clays, granite and iron show that clays to be more reflective than granite and iron. This result will help more in our further study on detecting these properties direct through remote sensing imagery and will be helpful in developing new indexes and selection of threshold value on shrines material in case study of Lembah Bujang. Simultaneously, a possible immensity of shrines area to be preserved from any future development expansion at once as a guidance to pursuing an area as official heritage site in beneficial a local authorities and decision makers.